Influência do método de preparação e performance catalítica para os catalisadores de Pd-La2O3-Al2O3 aplicados na reforma autotérmica do metano - França, Alexandre Bôscaro (2008)
Pd catalysts supported on Al2O3 and La2O3-Al2O3 (12 wt.% La2O3) were prepared by wetness impregnation method with aqueous solution of of palladium nitrate (1 wt.% Pd). The supports were obtained by conventional method (PdAl-Conv. and PdLaAl-Conv.) and two different sol-gel methods with Al-sec-butoxide/HNO3/Ethanol (PdAl-SG-Et. and PdLaAl-SG-Et) and Al-sec-butoxide/CH3COOH/sec-butanol (PdAl- SG-2But. and PdLaAl-SG-2But.). The catalysts were characterized by X-ray diffraction (XRD), BET surface area of catalysts were calculated from nitrogen absorption isotherm (SBET), FTIR-CO adsorption spectroscopy and autothermal reforming of methane (ATRM). XRD of precursors shows diffraction lines of boehmit for -SGEt. sample and shows diffraction lines of aluminum acetate for -SG-2But sample. No peaks of Pd or PdO were reveled in all catalysts samples. SBET for PdAl-SG-Et, PdLaAl- SG-Et and PdAl-SG-2But.catalysts shows type IV adsorption isotherm and H1 hysteresis and for PdLaAl-SG-2But catalyst shows type III adsorption isotherm and H3 hysteresis. FTIR-CO show that the adding of lanthana on γ-Al2O3 suppress CO adsorption in bridge form over Pd. The CO adsorption form is insensitive to presence of lanthana in catalysts obtained by sol-gel method. The intensity of bands of CO in bridge (LF) and linear (HF) show a LF/HF ratio of 4.8 to 2.3 for PdAl-Conv. and PdLaAl- Conv catalysts, respectively. The Pd catalysts supported on Al2O3 show higher deactivation with time on stream on ATRM reaction, which is assigned mainly to coalescence of Pd particle. La-containing catalysts are quite stable and H2/CO ratio depends to the synthesis method.